2016
DOI: 10.1016/j.compositesa.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Development of sizing-free multi-functional carbon fibre nanocomposites

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms AbstractHigh quality multi-walled carbon nanotubes (CNTs) grown at high density using a low temperature growth method are used as an alternative material to polymer sizing and is utilised in a series of epoxy composites reinforced with carbon fibres to provide improved physical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…This is a remarkable result considering the difference in V f between each sample (fibre volume fraction of (48.5 ± 0.5)% for the CFRP and (20.0 ± 2.0)% for the F-CFRP used in this test18.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…This is a remarkable result considering the difference in V f between each sample (fibre volume fraction of (48.5 ± 0.5)% for the CFRP and (20.0 ± 2.0)% for the F-CFRP used in this test18.…”
Section: Resultsmentioning
confidence: 61%
“…The weight change of the fabric during the growth process is displayed in Fig. 1h showing an initial reduction of weight of 1.7 wt.%, which occurs as a the result of the removal of the polymer sizing via a thermal annealing process518. The weight increase from this value is the result of weight gain by the CNT growth.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The most prevalent method to limit carbon fiber damage during the synthesis of CNT on carbon fiber substrates is the application of a barrier coating to the fiber surfaces, which limits catalyst contact with the fiber substrate. Common barrier coatings include silicon/silica [30][31][32][33][34][35][36], alumina [37][38][39] or pyrolytic carbon. [40][41][42] However, recently, we reported that the application of a modest potential difference minimized carbon fiber damage and improved the CNT coverage without the requirement for a barrier coating.…”
Section: Introductionmentioning
confidence: 99%